PRIORITAS PENGEMBANGAN OBJEK WISATA DI KOTA PADANG, PROVINSI SUMATERA BARAT - Iswandi Umar (Diponegoro University, 2018)
Indonesia is one country that has the potential for development of tourist beach. The number of visits to both domestic and foreign travel has increased every year. This study aims to determine the priority of tourism development in the coastal city of Padang. Priority tourism development is determined by the suitability of land and tourism development potential index. Suitability of land for tourist beach area using eight indicators, namely: water transparency, type of beach, shore depth, substrate, current speed, live coral cover, hazards, and accessibility. Index development potential attraction beach using five criteria: community acceptance, facilities and supporting infrastructure, cultural performances, industry support, and government support. The results showed attraction Muaro peevish beach is the main priority areas of tourism development in the coastal city of Padang, while the beach a tourist attraction Muaro Anai is the lowest priority.